Clothing needs of adults with Down syndrome - Malgorzata Matusiak; Nina Kuryłło (Communications in Development and Assembling of Textile Products)
A literature review showed that it is very difficult to find sufficient information concerning the market and clothes made specifically for people with Down syndrome. Especially in the case of adults with Down syndrome, it is a huge problem with clothing suiting their body shape as well as being stylish. The aim of the presented work was to analyze the needs of adults with Down syndrome in the field of clothing, and propose some useful guidelines for clothing designers. The aim was achieved by interviewing the parents/caregivers of adults with Down syndrome. Additionally, the anthropometric characteristic of women with Down Syndrome was analyzed based on the data from the literature concerning the exemplary profiles of women with Down syndrome. The analysis showed differences between body dimensions in the size charts intended for women without disability and the dimensions of the surveyed group of women.